Land Subsidence and Aquifer‐System Storage Loss in Central Mexico: A Quasi‐Continental Investigation With Sentinel‐1 InSAR - F. Cigna; D. Tapete (Geophysical Research Letters)
Abstract Aquifers play an important role in addressing water needs worldwide. When overexploited, they may lose storage and compact, causing land subsidence and impacts on urban landscapes. Using Sentinel‐1 satellite imagery, we perform the largest ever‐made Interferometric Synthetic Aperture Radar (InSAR) survey over Mexico, across a 700,000 km2 area hosting >85.2 million inhabitants. We estimate present‐day subsidence rates for yet unmapped and well‐known hotspots (e.g., −45 cm/year in Mexico City), and compute compaction volumes at >300 aquifer‐systems (up to −60 hm3/year at Mexico City Metropolitan Area). InSAR‐derived aquifer‐system compaction generally correlates well with groundwater deficits, extractions and storage changes from management reports. Semi‐theoretical relationships for the whole Central Mexico and hydrological‐administrative regions VII, VIII, and XIII, enable the assessment of compaction rates and volumes resulting from groundwater exploitation. These could be used to inform groundwater management strategies towards adaptation to climate change and future needs of a growing population.